2019
DOI: 10.1111/cea.13500
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac safety of second‐generation H1‐antihistamines when updosed in chronic spontaneous urticaria

Abstract: The symptoms of chronic urticaria, be it chronic spontaneous urticaria (CSU) or chronic inducible urticaria (CindU), are mediated primarily by the actions of histamine on H1 receptors located on endothelial cells (the weal) and on sensory nerves (neurogenic flare and pruritus). Thus, second‐generation H1 antihistamines (sgAHs) are the primary treatment of these conditions. However, many patients are poorly responsive to licensed doses of antihistamines. In these patients, the current EAACI/GA2LEN/EDF/WAO guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 95 publications
0
27
0
Order By: Relevance
“…In contrast, cetirizine 10 mg increased the number of errors at ground level and, at the simulated altitude (4000 m), additional impairment was observed in cetirizine 10 mg recipients in a distributive attention test 56 . Bilastine has no significant effect on QTc interval 58,59 , and there is no evidence of cardiotoxicity even when updosed up to four times the standard licensed dose 60 . Based on the European Medicines Agency (EMA) periodic safety update report of post-marketing activity, a cumulative review of hypersensitivity reactions was performed for bilastine.…”
Section: Safety In Adultsmentioning
confidence: 95%
“…In contrast, cetirizine 10 mg increased the number of errors at ground level and, at the simulated altitude (4000 m), additional impairment was observed in cetirizine 10 mg recipients in a distributive attention test 56 . Bilastine has no significant effect on QTc interval 58,59 , and there is no evidence of cardiotoxicity even when updosed up to four times the standard licensed dose 60 . Based on the European Medicines Agency (EMA) periodic safety update report of post-marketing activity, a cumulative review of hypersensitivity reactions was performed for bilastine.…”
Section: Safety In Adultsmentioning
confidence: 95%
“…Therefore, concomitant administration of rupatadine with known CYP3A4 inhibitors (e.g. grapefruit, ketoconazole, erythromycin) is not recommended [51][52][53][54][55][56][57][58][59][60][61]. In contrast, no clinically relevant changes in plasma levels were observed when rupatadine and azithromycin were coadministered [57].…”
Section: Rupatadine Pharmacological Propertiesmentioning
confidence: 99%
“…Systemic exposure to rupatadine after food intake increased by 23% compared with that under fasting conditions and Tmax was delayed by 1 hour, but exposure to its metabolites remained unaffected. These changes did not show clinical consequences, and therefore, rupatadine can be administered with or without food [16,17,[51][52][53][54][55][56][57][58][59][60][61].…”
Section: Cetirizinementioning
confidence: 99%
“…[1] The most commonly used drug is the second-generation H1 receptor antagonist, which can control the occurrence of CU during clinical use. Mauro Cataldi et al [7] considered in detail Second-Generation H1-Antihistamines such as cetirizine, ebastine, fexofenadine, loratadine, desloratadine, mizolastine, and rupatadine and concluded that all these drugs have an excellent safety pro le with no evidence of cardiotoxicity even when updated up to four times their standard licensed dose. [7] The main option in therapies aimed at symptomatic relief is to reduce the effect of mast cell mediators such as histamine, PAF, and others on the target organs.…”
Section: Rationalementioning
confidence: 99%
“…Mauro Cataldi et al [7] considered in detail Second-Generation H1-Antihistamines such as cetirizine, ebastine, fexofenadine, loratadine, desloratadine, mizolastine, and rupatadine and concluded that all these drugs have an excellent safety pro le with no evidence of cardiotoxicity even when updated up to four times their standard licensed dose. [7] The main option in therapies aimed at symptomatic relief is to reduce the effect of mast cell mediators such as histamine, PAF, and others on the target organs. Many symptoms of urticaria are mediated primarily by the actions of histamine on H1-receptors located on endothelial cells and on sensory nerves.…”
Section: Rationalementioning
confidence: 99%